Fabrication of Sustainable Roller-compacted Concrete Pavement containing Plastic Waste as Fine and Coarse Aggregate - Almajeed, Shahad Qais Abd; Abbas, Zena K. (Engineering, Technology & Applied Science Research, 2024)
The primary goal of this practical lab analysis was to obtain a sustainable and eco-friendly Roller-Compacted Concrete (RCC), by lowering the consumption of natural resources and energy and utilizing plastic waste. The experiment performed involved six RCC mixes with partial weight replacement of coarse or fine aggregate of specified percentages with waste plastic along with a reference mixture (R.M), utilizing different curing methods, namely spraying with water two times per day, immersing in water, and utilizing ISO SMART CURING W 1035 material. Three types of plastic were used in the analysis: polyvinyl chloride (PVC) as coarse aggregate replacement and polyethylene terephthalate (PET) and high-density polyethylene (HDPE) as fine aggregate replacement. The mixes were tested regarding compressive, flexural, and splitting tensile strength. The results of the study indicate that the RCC containing 10% PVC (CP10) exhibited a reduction in compressive strength of 5.25, 5.69, and 5.99% for water, spray, and coating curing, respectively at 28 days related to the R.M, followed by the mix including 20% PVC (CP20) with a decrease ratio of 12.79, 13.52, and 13.20%. Mixtures with 5% PET and HDPE (FP5, FH5) can be accepted, since their results were nearest to R.M with a percentage decrease of 4.16, 3.52, and 3.74% for PET and 3.18, 3.13, and 3.14%for HDPE. Treating with coating material achieved the best results, exhibiting improvement in compressive, flexural, and tensile splitting strength, while the water spray method performed worse than water curing.